(untitled) (Web of Teachers: Inderscience Research, 2025)
Mobile-health (mHealth) applications are widely downloaded globally, yet robust evidence of their impact on health behaviors in Central Asia remains limited. We evaluate the associations between the regular use of health-related mobile apps and four key behavioral health domains—physical activity, mental health, nutrition, and sleep—in a sample of Uzbek adults. We surveyed 200 adults in Uzbekistan—100 regular health-app users and 100 non-users. All questionnaire totals were standardised across the whole sample (z-scores, μ = 0, σ = 1) and expressed on a 0–100 T-metric (μ = 50, σ = 10). Users reported much higher physical-activity scores than non-users (Δ = 10.4 T-points; t(196) = 7.31; p <0.0001; Cohen’s d = 1.04). A moderate and statistically significant difference also favoured users for mental health (d = 0.67; Holm-adjusted p = .00001). Nutrition (50.9 ± 7.3 vs 49.1 ± 7.1; d = 0.18) and sleep quality (49.7 ± 9.5 vs 50.3 ± 10.6; d = 0.17) did not differ meaningfully. An ANCOVA that adjusted for age, sex, education and chronic conditions reproduced the same pattern. The findings show a strong positive association between regular use of activity-focused apps and self-reported exercise levels, whereas links with mental health, diet and sleep are weak or absent.